2017
DOI: 10.3174/ajnr.a5129
|View full text |Cite
|
Sign up to set email alerts
|

Brain Perivascular Spaces as Biomarkers of Vascular Risk: Results from the Northern Manhattan Study

Abstract: Background Dilated perivascular spaces (PVS) in the brain are associated with greater arterial pulsatility. We hypothesized that PVS identify individuals at higher risk of systemic and cerebral vascular events. Methods Stroke-free participants in the population-based Northern Manhattan Study had brain MRI performed, and were followed for myocardial infarction, any stroke, and death. Imaging analyses distinguished PVS from lesions presumably ischemic (LPI). PVS were further subdivided into lesions with diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
4
56
1
Order By: Relevance
“…2 In a population-based study of older adults, stroke-free subjects with higher burden of EPVS had higher rate of carotid atherosclerosis 27 as well as higher risk of mortality, incidence of any stroke or any other vascular events in a 10-year follow-up. 28 EPVS in the basal ganglia had larger impact on poststroke HRQoL than in the centrum semiovale which were found in this study. They also had different effects on the subscores of the SSQoL.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…2 In a population-based study of older adults, stroke-free subjects with higher burden of EPVS had higher rate of carotid atherosclerosis 27 as well as higher risk of mortality, incidence of any stroke or any other vascular events in a 10-year follow-up. 28 EPVS in the basal ganglia had larger impact on poststroke HRQoL than in the centrum semiovale which were found in this study. They also had different effects on the subscores of the SSQoL.…”
Section: Discussionsupporting
confidence: 65%
“…Further, stroke patients with higher degree of EPVS in the basal ganglia had a higher risk of recurrent stroke . One possible explanation for these findings was that more EPVS meant more severe underlying microvascular lesions and aggregation of vascular risk factors, which, in turn, increased the incidence of vascular events . Vascular risk factors and vascular events could explain the poor HRQoL in stroke .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired arterial stiffness (13) and increased pulsatility index (14) were found in severe MCA stenosis. Moreover, previous studies showed increased cerebrovascular pulsatility and arterial stiffness were related to increased BG-EPVS (15)(16)(17). Based on these findings, it is reasonable to imagine that BG-EPVS might be more prevalent in patients with severe MCA atherosclerosis.…”
Section: Introductionmentioning
confidence: 75%